(untitled) (Research, Society and Development, 2022)
The use of refurbished equipment is considered a sustainable alternative, capable of reducing acquisition costs in organizations. This article aims to compare the performance of new and refurbished off-road trucks in a mining company. For this, a case study was carried out, using maintenance performance indicators: Physical Availability (DF), Mean Time Between Failures (MTBF), and Mean Time To Repair (MTTR). As a result, it was possible to verify that although the new trucks have presented better results in the indicators, the average availability of the refurbished trucks are within the performance standards indicated by the customer. A trend of improvement in the performance of refurbished trucks was verified with joint maintenance actions to reduce premature failures, bringing their performance closer to that of new trucks.